HUBUNGAN ANTARA STRUKTUR ORGANISASI DENGAN EFEKTIFITAS ORGANISASI DI PESANTREN - Djamaluddin Perawironegoro (POTENSIA: Jurnal Kependidikan Islam, 2019)
The purpose of this research is to develop the model of organizational structure in pesantren that have the relationship and an impact with organizational effectiveness. This research is quantitative research with structural equation modeling analysis. Sources of data from 273 managers were collected from 98 various profit and non-profit unit in Pesantren. To analyze data the researcher used a Partial Least Square (PLS-SEM) with Smart PLS 2.0 as a tool. The result from this research is correlation result 0,553, it’s mean that there is correlation between organizational structure and organizational effectiveness at middle level. The result from determinant coefficient showed 0,305 (30,5 %) that there is significant effect from organizational structure toward organizational effectiveness in pesantren.